‘Sites of memory’: an urban perspective - Mitroiu, Simona (Acta Scientiarum. Human and Social Sciences, 2014)
The collective identity has, as main references, various ‘sites of memory’ that are not only mental constructions, but also physical places related to the collective common space, shared by a community – the city. The transformations occur at the level of cityscape, transformations that have as their object the sites of memory, and determine a series of modifications at the level of the collective narrative identity. This paper explores a range of political changes imposed at the cityscape level, approaching different aspects of the processes involved. Presenting some relevant concepts in order to sustain the theoretical frame of the research, in its second part the paper focuses on the complex relation between memory, narrative identity, city and political power, revealing the dynamics of this relation and of the representation of the sites of memory.